The Dialogue on the Implementation of Corporate Social Responsibility Standards as a Promoter of the Proper Exercise of Rights: An Approach Based on the Discourse Ethics of Jürgen Habermas - Zambrano Chavez, Gustavo Arturo (2010)
The purpose of this article is to contribute to clarify a discussion on the development scenario of the stakeholders in which the dialogue between companies and local groups could be guaranteed. The frame of reference that the author takes is the foundation of Habermas's discourse ethics. As an essay, the author starts from practical ethics and legal theory, presents the most important premises about what corporate social responsibility is from the interest group theory approach; with an emphasis on local communities; In addition, he tries to explain the reasons that justify why companies —especially extractive ones— have social responsibilities, exposing the most outstanding criticisms against the CSR approach and how such arguments suffer from drawbacks in their foundation. He proposes to understand CSR from the importance of dialogue understood from the theory of discursive ethics of Jürgen Habermas. Finally, it is about demonstrating how this habermasian approach of dialogue in CSR consolidates the proper exercise of rights.